DeepFakes- The Digital Threat in the Real World - Mankoo , Sandeep Singh (Gyan Management Journal, 2023)
Objectives: Understanding and Tackling the alarming surge of Digital Imposters known as the world of DeepFakes. Methods: Using Artificial Intelligence based Deep Machine Learning software; Cyber Forensics; Physical mind awareness and alertness! Deepfakes use Artificial Intelligence and Deep Machine Learning techniques to make fake images, of people and events, which are as attractive/ authentic as the original. Deepfakes is the next big Challenge in Cyber Security, taking the Security mindset to the next high level. Findings: On date we have no Specialized High-Tech support at hand to handle such an extremity. We can’t even imagine that if it was a crisis. The impact might be ruinous; it can be anything. In one of the recent live impersonation cases, A Mayor of Berlin thought he was having an online meeting with former boxing champion and current mayor of Kyiv, Vital Klitschko, but later on turned out to be a conversation with a deepfake, an AI generated fake videotape, looking real and authentic. Previous DeepFake videos had some tell-tale signs that a commodity/ person/ event wasn’t real; edit or odd movements. Not presently. In recent Delhi Elections, the BJP Candidate Mr. Manoj Tiwari fabricated his old speech on “Citizenship Amendment Act” into a political campaign speech to reach different linguistic voter bases, especially Haryanvi voters. Tiwari did not have any knowledge about Haryanvi, but made his political campaign message reach Haryanvi voters through DeepFake Technology. Novelty: Massive Online Videos on Internet!